The Effect of Training on Employee Motivation and Performance at the Secretariat of the DPRD of North Sumatra Province - Yesin Kristiani Sarumaha; Ahmad Aswan Waruwu (Universitas Muhammadiyah Enrekang, 2022)
The research was conducted to find out how the direct and indirect influence of Training (X) on Employee Performance (Y) at the Secretariat of the DPRD of North Sumatra Province through Motivation (Z). The population in the research was 107 civil servants with the number of samples used as many as 52 civil servants using the Slovin formula. The sampling technique used was purposive sampling. This research was conducted in 2022. The data used were primary data taken directly from respondents using a questionnaire. This research used quantitative data that was processed with SPSS 24.0 with path analysis. The results of the path analysis showed that training directly had a positive and significant effect on motivation with the Standardized Coefficients Beta Training value of 0.900 with a significant 0.000. Training directly had a positive and significant effect on employee performance with the Standardized Coefficients Beta Training value of 0.931 with a significant value of 0.000. Motivation directly had a positive and significant effect on employee performance with a value of Standardized Coefficients Beta Training of 0.942 with a significant value of 0.000. The results of the path analysis also showed that indirectly training did not have a significant effect on employee performance through motivation, which meant that motivation was not able to mediate the effect of training on employee performance. The indirect effect of training on employee performance through motivation was 0.848 which was smaller than the direct effect of training on employee performance of 0.931.